A Case of Laryngeal Cryptococcosis that Responded to Itraconazole - Maezumi, Sorane; Motohashi, Ray; Shoji, Yusuke; Tsukahara, Kiyoaki (Case Reports in Otolaryngology, 2023)
Laryngeal cryptococcosis is a rare condition. While there is no reliable evidence regarding the treatment of laryngeal cryptococcosis, oral fluconazole was successful in most previous cases. We experienced a case where we could not continue fluconazole because of adverse drug effects. An 88-year-old female was referred to our department with a 5-month history of sore throat and cough. She had used oral steroids and a corticosteroid inhaler for poorly controlled asthma. Flexible laryngoscopy showed leukoplakia of the vocal cords and subglottic mucosa, and biopsy revealed cryptococcal infection. We started the treatment with fluconazole but changed to itraconazole because of adverse events. Since laryngoscopy performed 6 months later was unremarkable and drug interactions had occurred, we stopped the itraconazole use at 6 months. Our experience suggests that itraconazole is also useful for treating laryngeal cryptococcosis.